Pemberdayaan UMKM Kelapa Gongseng Aceh Melalui Pemasaran Berbasis Digital Dalam Upaya Menembus Pasar Global - M Saleh; M. Rasyidin; Hamdani; Afkar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Micro, small and medium enterprises (MSMEs) are one of the primary drivers of the Indonesian economy, as a result if the MSME sector is disrupted, the national economy could also be eroded. According to the Central Statistics Agency (BPS), in 2021 the number of MSMEs will reach 65.46 million units. Maju Sejahtera is an MSME in Panjang Mesjid Village, Panjang Subdistrict, Bireuen Regency, Aceh Province which operates in the food service sector producing gongseng coconut. This group has been running its business since 2019 and produces around 30-50 kg of gongseng coconut every week with a market selling price of around 50 thousand per kilogram. This fishing business group has 5 freelance workers and has assets of around 24 million rupiah. However, recently the production and sales of gongseng coconut have decreased, this is due to the Covid-19 pandemic that has hit the world, so it indirectly affects the demand for gongseng coconut. Before the Covid-19 pandemic, MSME Maju Sejahtera had an obstacle in running a business in the field of product marketing, the system that had been used was still traditional, namely marketing to local traders or the products were taken by collectors, then MSME Maju Sejahtera had no business management or financial management, during This often causes problems in financial management, namely business finances are often combined with family finances so it is very difficult to see profits in the business. The aim of this service activity is to increase partners' knowledge in business management and digital marketing. The implementation method is to provide business management training and direct digital sales practice through marketplaces and social media. The result of this activity is an increase in partners' knowledge about business management and better digital marketing.